Dry phase conditions prime wet‐phase dissolved organic matter dynamics in intermittent rivers - Rubén del Campo; Rosa Gómez; Gabriel Singer (Limnology and Oceanography, 2019)
During the dry phase of intermittent rivers, diverse particulate organic materials, such as leaf litter or macrophytes, remain on dry riverbeds. Together with riverbed sediments, these organic substrates are exposed to various environmental conditions that can alter their chemical composition, with potential implications for later use by heterotroph consumers when flow is re‐established. Here, we investigate how different environmental conditions during the dry phase alter quantity, composition, and biodegradability of dissolved organic matter (DOM) leached from dry riverbeds. To this end, we simulated the “preconditioning” of various DOM sources during a dry phase of 60 d under conditions mimicking open‐ and closed‐canopy rivers. Over the whole experiment, we produced leachates for measurements of nutrients and dissolved organic carbon (DOC) concentration, DOM characterization by absorbance and fluorescence measurements and ultrahigh‐resolution mass spectrometry, and DOM biodegradability. We found that rain, solar radiation, and its associated heat greatly affected leached DOM quantity, composition, and biodegradability. Under open‐canopy conditions, sporadic rain caused the impoverishment of nutrients and DOC by leaching, whereas intense solar radiation and associated heat resulted in a drop of DOM quality and biodegradability by accelerated humification of DOM. In contrast, the preconditioning of DOM sources under a closed canopy barely affected DOM quality and biodegradability because of the protection from rain, solar radiation, and heat by the forest vegetation. Our results suggest that contrasting environmental conditions during the dry phase in open‐ vs. closed‐canopy intermittent rivers can translate into radically different DOM processing during the early wet phase.